2016
DOI: 10.15376/biores.11.1.2020-2029
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Dimensional Stability of Decorative Papers under Moistening

Abstract: A crucial problem for laminate producers is the dimensional instability of decorative papers during soaking in aqueous solutions, but the source of this dilemma is not completely understood yet. In this study, eight commercial decorative papers of similar fiber composition and sizing were analyzed for their structural, physical, and mechanical properties. These properties were examined for their correlations to the dimensional stability of papers when moistened, as assessed by the wet stretch dynamics. Structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Accordingly, Figueiredo et al [161] found that the wet expansion under tension is strongly affected by the filler content. The excessive addition of inorganic fillers reduced the paper web dimensional stability in the cross direction (expansion of *2.4 to *2.75% for ash contents of *23 to *36%).…”
Section: Fillersmentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, Figueiredo et al [161] found that the wet expansion under tension is strongly affected by the filler content. The excessive addition of inorganic fillers reduced the paper web dimensional stability in the cross direction (expansion of *2.4 to *2.75% for ash contents of *23 to *36%).…”
Section: Fillersmentioning
confidence: 98%
“…As already explained, the expansion of single fibers is higher in the transverse direction than in the longitudinal direction. The expansion of paper in cross direction (CD) is up to 7 times higher than in the machine direction (MD) [25,161,185,186]. However, fibers are not 100% parallel in reality and the orientation is determined by several variables of the papermaking process.…”
Section: Fiber Orientationmentioning
confidence: 99%
“…45 For an increment Dy w E 0.04 kg kg À1 , they found a strain amplitude De CD E 0.14%. Figueiredo et al measured the wet expansion of different paper types 46 and found values in the range of De CD E1.5-3%. number L490) and a digital displacement gauge (Mitutoyo, model number ID-H0530).…”
Section: A Materials and Materials Propertiesmentioning
confidence: 99%
“…While PCA selects a direction that retains the maximum structure of data on a reduced dimension, SDA selects a direction that achieves maximum separation between given sample classes (Berrueta et al 2007, Li et al 2014Figueiredo et al 2016). Stepwise regression was introduced to screen key VOCs components as characteristic chemicals to make a classification.…”
Section: Principal Component Analysismentioning
confidence: 99%